Where was the Afro in Afro-Asian Solidarity? Africa's 'Bandung Moment' in 1950s Asia. - McCann, Gerard (Journal of World History, 2019)
Africans are staged but not often heard in discussions of the "Bandung moment," a high-watermark of decolonial possibility and Afro-Asian connection. This article foregrounds the agency and perspectives of African activists who travelled across Asia in the 1950s. In Delhi, Rangoon, and Bandung, Africans engaged, co-produced, and made useable the dialogical Afro-Asian world to deconstruct colonialism and engineer alternative futures. The article tracks these dynamics through three interlocked arenas of Afro-Asian affinity: journeys of African students to India from the 1940s; African participation in the Asian Socialist Conference in Burma, 1953–1956, and, as the geographies of Afro-Asianism shifted, radicalized, and splintered, African activism within the Afro-Asian Peoples' Solidarity Organization in Cairo from 1957. It reveals how the overlapping internationalisms of these fora reinforced a dyad of anti-colonial politics and development in the construction of African nationhood and pan-African community. This article breaks new ground in privileging the Afro in Afro-Asian.